(untitled) (Global Journal of Science Frontier Research, 2024)
Currently there is a general concern among consumers to purchase goods increasingly healthy that not only provide the necessary nutrients but also beneficial compounds with functional properties and antioxidant activity Because of this there has been an increased consumption of vegetables of the Brassicaceae family especially brassicas Thus in this research work two types of brassicas broccoli and Savoy cabbage were evaluated and it was found that broccoli had a higher content of functional compounds But functional compounds are absorbed and used in different ways when they are digested so besides knowing the content of these compounds in foods it is necessary to know their bioavailability which will help meet the health properties of food to optimize the diet and to establish nutritional recommendations Therefore the brassicas were digested by a model of in vitro digestion obtaining that the percentages of bioaccessibility of these biocompouds were between 1 5 and 41 for Parthenon broccoli and between 2 4 and 34 for Dama Savoy cabbage